Foreign-trained dentists' reflections on access to care after participating in a community-based dental education curriculum - Smith, Patrick Dean; Noorullah, Khatija; Syed, Syeda; Iqbal, Laila; Tomar, Scott L. (Frontiers in Oral Health, 2022)
Many people suffer poor oral health due to dentists not providing care to them. The number of foreign-trained dentists in the US is increasing, yet little is known about their involvement in providing care to underserved populations. Dental education programs use community-based dental education (CBDE) to expose dental students to access to care issues, and encourage them to provide care to underserved populations upon graduation. The aim of this study was to assess foreign-trained dentists’ attitudes about access to care issues after completing a CBDE course at a dental school in the Midwest. Fifty-two dentists participated in the CBDE program from 2018-2019, as part of an advanced standing curriculum, and completed guided, reflective essays. Forty-seven dentists agreed to have their essays anonymously coded for research. Four researchers reviewed the essays independently, developed a coding scheme, and recoded to agreement. The main themes dentists mentioned were the affect of the CBDE program on enhancing their clinical skills, fostering an awareness of healthcare system inadequacies, as well as an awareness of how specific social determinants limit access to care, and helping to encourage a sense of personal and professional responsibility to address access to care issues. This study highlights the value of CBDE on helping future dental providers learn about and reflect on access to care issues. It also provides insight into foreign-trained dentists’ attitudes about access to care issues, and supports their participation in CBDE programs to foster their contributions in addressing access to care issues in the US.